Optimalisasi lingkungan kelas dalam membangun kemandirian anak usia dini di TK Bina Nurani Surabaya - Virnanda; Amanda Dwi Lestari; Zahwa Rahman; Noor Fahima; M. Bahri Musthofa (Liberi, 2026)
The purpose of this study was to analyze how the physical, social, and psychological learning environment at Bina Nurani Kindergarten in Surabaya is optimally managed to foster independence in early childhood. The method used in this study was descriptive qualitative, with data collection techniques including direct observation, interviews, and documentation in the Kindergarten Group. The study shows that managing a clean, healthy, and safe classroom can help overcome geographical constraints that limit outdoor play areas in densely populated urban areas. The main factors influencing children's learning environment are the nature and communication style of teachers who are friendly, polite, and democratic. The implementation of two-way communication without applying emotional pressure or using harsh methods, as well as providing positive reinforcement in the form of star stickers or continuous verbal praise, successfully creates a sense of psychological security in children. This non-threatening classroom atmosphere is the main foundation that encourages children to dare to try new things, ask questions actively, and express themselves without fear of making mistakes. The study concluded that success in building a comfortable environment for children in early childhood education institutions is more influenced by warm interpersonal relationships and a calm psychological classroom atmosphere, rather than just the presence of luxurious physical facilities.